1997
DOI: 10.1021/jp971773l
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Ions in Organic Solvent and Its Significance in the Gibbs Energy of Ion Transfer between Two Immiscible Liquids

Abstract: Various kinds of cations (alkali and alkaline earth metal ions, Me4N+, Et4N+, n-Bu4N+, and tetraphenylarsonium ion) and anions (halide ions, SCN-, ClO4 -, NO3 -, and tetraphenylborate ion) have been extracted from water to nitrobenzene (NB) using several extractants:  viz. tetraphenylborate and dipicrylaminate for the cations; n-Bu4N+, n-Pen4N+, n-Hep4N+, and tris(1,10-phenanthroline)iron(II) for the anions. The determination of water content in NB by means of the Karl Fischer method has confirmed that some wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
122
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(147 citation statements)
references
References 35 publications
24
122
0
Order By: Relevance
“…Figure 3 (solid line) shows the partial ion-water oxygen rdf for sodium. Integration under the first peak gives a coordination number of essentially 4 (see Table I), a value which agrees with that obtained for sodium ions in an aqueous solution from a range of measurements and simulations [19][20][21][22][23][24]. The cation therefore retains its normal hydration shell in this solution.…”
supporting
confidence: 84%
“…Figure 3 (solid line) shows the partial ion-water oxygen rdf for sodium. Integration under the first peak gives a coordination number of essentially 4 (see Table I), a value which agrees with that obtained for sodium ions in an aqueous solution from a range of measurements and simulations [19][20][21][22][23][24]. The cation therefore retains its normal hydration shell in this solution.…”
supporting
confidence: 84%
“…The concentrations of water in the pure organic solvents equilibrated with water were determined and are listed in Table 1 38 and Kd,L = 5.50 (CTC), 39 22.8 (o-DCB), 39 24.5 (CB), 39 20 (BZ), 40 250 (CF), 41 85 (1,2-DCE), 42 and >100 (DCM) 43 for B15C5, in which the B18C6 system is shown in Fig. 1 as an example.…”
Section: Hydration Number Of Free B15c5 and B18c6mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Particularly, in the solvent extraction study, since the solutes in the water-saturated organic solution are discussed, hydration of the solutes in the organic phase is a very important subject. It has been demonstrated that the water molecules are coextracted with the metal ions, [11][12][13][14] the metal complexes, [14][15][16][17] and the inorganic anions 2,3,[18][19][20] into the organic solvents, and the mean hydration numbers of these solutes in the organic phase were determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This similarity originates from the fact [73] that ions are transferred to the organic phase together with the water molecules constituting their first solvation shell [42,44], and hence the unfavourable case (i.e., methane in water, and hydrated ions in DCE) involves water-apolar contacts in both cases. The energy cost corresponding to these unfavourable contacts should primarily depend on the number of such contacts, i.e., the number of water molecules constituting the first hydration shell of the penetrant (as in the case of methane in water these molecules are in contact with the apolar methane molecule, whereas in the case of the hydrated chloride ion in DCE these waters are in contact with the surrounding DCE molecules).…”
Section: Darvas Et Almentioning
confidence: 99%